TUBA1A-GLI1 fusion in a soft tissue myoepithelial neoplasm - Yajuan J. Liu; Michael J. Wagner; Edward Y. Kim; Eleanor Y. Chen (Elsevier, 2021)
Several types of benign and malignant neoplasms harboring GLI1 gene fusions with various partner genes, including ACTB, MALAT1 and PTCH1, have been described. These neoplasms show a spectrum of morphologic features and immunohistochemical profiles. However, the GLI1 gene fusion has not been described in soft tissue myoepithelial neoplasms previously. In this study, we reported a novel TUBA1A-GLI1 gene fusion in soft tissue neoplasm occurring in the chest wall of a 35-year-old male. The neoplasm shows morphologic features and immunophenotype of myoepithelial differentiation. FusionPlex analysis detected TUBA1A-GLI1 fusion in the neoplasm. The fusion transcript is comprised of 3' end of exon 1 of TUBA1A and 5' end of exon 6 of GLI1, retaining the FOXP coiled-coil domain and the DNA-binding zinc finger domains of GLI1. Promoter swapping with the TUBA1A (tubulin alpha 1a) gene likely leads to deregulation of GLI1 expression and its downstream targets. Despite the clinical presentation of multifocal disease and regional lymph node metastasis, the neoplasm in our case study appeared to be stable in a 10-month follow-up, suggesting that this neoplasm likely pursues an indolent clinical course. This study expands the morphologic and immunohistochemical spectrum of the neoplasms with GLI1 gene fusions and identifies a novel fusion in soft tissue myoepithelial neoplasms. As the TUBA1A-GLI1 fusion event likely results in activated GLI1 expression, targeting the Hedgehog pathway is a potential therapeutic option for treatment of patients with this neoplasm.